Explorative assessment of factors affecting child immunization in Wonago district, Gedeo zone, South Ethiopia - Tadesse, Henok; Deribew, Amare; Woldie, Mirkuzie (Archives of Medical Science, 2009)
Introduction: Immunization provides protection from infectious diseases, including some potentially life threatening diseases such as measles, whooping cough, and tetanus. However, factors affecting child immunization were not well studied in Ethiopia. The objective of this study was to explore factors associated with child immunization in Wonago district, South Ethiopia. Material and methods: A cross-sectional qualitative study employed both focus group discussions and in-depth interviews using focus group discussion and in-depth interview guides. A total of 6 focus group discussions and 22 in-depth interviews were carried out with community representatives in Wonago district. Thematic analysis of transcripts of focus group discussions and in-depth interviews was made and the data were transcribed verbatim. Also, overall interpretation was performed by relating thematic areas to each another and explaining how the various concepts related to the study questions. Result: Most of the in-depth interviewees and focus group discussants were knowledgeable regarding vaccines and vaccination. However, a few of the mothers and traditional healers do not know about vaccines, its benefits and side effects. Some of the focus group discussants explained that fear of side effects of vaccines could prevent mothers from having their children vaccinated. Most of the interviewees of in-depth interviews and focus group discussants raised different obstacles to vaccination in children. Of these, lack of awareness about immunization, misunderstanding of side effects, absence of electricity in the presence of refrigerators, few immunization sites on an outreach basis, misunderstanding of health extension services (more preventive services though the community demand is curative) and seasonal events especially during the time of coffee collection. Conclusions: In summary, the results of this study demonstrated that knowledge regarding vaccination, its benefits and side effects and help of health professionals at immunization sites are closely related to child vaccination behaviours in women or immediate care takers in rural districts of Ethiopia. All of these factors should be considered fully when developing strategies for child vaccination.